(untitled) (Journal of Applied and Natural Science, 2018)
Geometric increase in population coupled with rapid urbanization, industrialization and agricultural development are causing increased pressure on global water resources. Agriculture is the largest consumer of fresh water resources, thus the scope of enhancing water productivity in agriculture is taken to be the priority area of research. The right amount and frequency of irrigation is essential for optimum use of limited water resources for crop production as well as management. A field experiment with split plot design was carried out during November to February 2015-16 at PFDC (Precision Farming Development Centre), Water Technology Centre, IARI, New Delhi to study the effect of different irrigation levels and frequencies on Broccoli (Brassica oleracea var. italica) under drip irrigation. The experiment included three levels of irrigation frequencies: N1 (once every day), N2 (once every 2 days) and N3 (once every 3 days) with different irrigation levels of 100, 80 and 60 % of crop evapotranspiration (ETc). Results revealed that drip irrigation frequency significantly (p<0.05) affected the broccoli yield. The maximum yield (24.46±0.18 t/ha) was obtained with 80% of ETc with once in 2 days irrigation followed by 100% of ETc with once in 2 days. Lowest yield (16.53±0.1 t/ha) was obtained at 60% of ETc at once in 3 days irrigation. Overall, it was observed that irrigation on 80% of ETc with once in two days is an appropriate cycle for optimum yield of broccoli.